THE EFFECTIVENESS OF ONLINE LEARNING AT STKIP MUHAMMADIYAH BATANG - Fahmi Surya Adikara; Dwi Cahaya Nurani; Yanuar Akhmad; Mar'atul Faida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The Corona Virus Disease (COVID-19) outbreak resulted in the changing of learning system from face-to-face learning to online learning. This policy seemed to be inefficient in lecturing since this changing was considered to make it difficult for students to understand the material or, in other words, students could not understand the material optimally. The purpose of this study was to measure the effectiveness of online learning carried out at STKIP Muhammadiyah Batang, so that it was expected to provide contributions and solutions for online learning during the Covid-19 pandemic. This was a qualitative descriptive study by using an online survey method. The primary data collection in this study was carried out by distributing questionnaires online to 30 respondents who were students of PGSD STKIP Muhammadiyah Batang. The students were at semester 2 and semester 4. Online learning at STKIP Muhammadiyah Batang was considered ineffective due to many obstacles experienced by students. Moreover, students expected the mixed learning method (online / face-to-face).